1989
DOI: 10.1105/tpc.1.9.913
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of avenin proteins and the expression of their mRNAs in developing oat seeds.

Abstract: We have isolated and characterized cDNA clones encoding avenins, the prolamine storage proteins of oat seeds. Sequence analysis shows that avenins are a related group of polypeptides and that their mRNAs differ from each other by point mutations and small insertions and deletions. Avenin proteins have structural homology to the a/@-gliadins and r-gliadins of wheat, the B-hordeins of barley, and the r-secalins of rye. Hybridization analysis of DNA from various diploid, tetraploid, and hexaploid oat species show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 27 publications
5
22
1
Order By: Relevance
“…The spectra of the avenin fractions of the different oat varieties obtained by MALDI-TOF MS and the electrophoretic distribution of the prolamins by SDS–PAGE revealed distinct patterns that could allow their further identification (figure 2). In both MALDI-TOF MS and SDS–PAGE, the distribution of molecular weights ranged between 19 and 31 kDa, in agreement with previous work describing avenins 18 19. The number and relative intensity of the peaks obtained by MALDI-TOF MS in the nine oat cultivars were very variable, indicating that oats differ in their avenin complement.…”
Section: Resultssupporting
confidence: 88%
“…The spectra of the avenin fractions of the different oat varieties obtained by MALDI-TOF MS and the electrophoretic distribution of the prolamins by SDS–PAGE revealed distinct patterns that could allow their further identification (figure 2). In both MALDI-TOF MS and SDS–PAGE, the distribution of molecular weights ranged between 19 and 31 kDa, in agreement with previous work describing avenins 18 19. The number and relative intensity of the peaks obtained by MALDI-TOF MS in the nine oat cultivars were very variable, indicating that oats differ in their avenin complement.…”
Section: Resultssupporting
confidence: 88%
“…lb) than globulin cDNA, as has already been reported by Chesnut et al (1989). Two fragments correspond to bands with an intense autoradiograph signal (4.8 and 3.8 kb).…”
Section: Resultssupporting
confidence: 79%
“…Landry et al 1987, comparing various sources of probes for their efficiency in detecting RFLP in lettuce, concluded that an increased detection of polymorphism in multiple-copy sequences could be the result of independent mutations in the different copies of the gene in the presence of a released selection pressure. Indeed, avenin and globulin genes are known to be present in 25 and 50 copies, respectively, per haploid genome of A. sativa (Chesnut et al 1989). The present results show that the two probes hybridize with many genome sequences, and a globulin copy number reconstruction experiment confirms the large number of sequences for each fragment.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Avenin is the prolamin of oats (considered the sixth most important crop globally) and has some interesting properties. Avenin resembles gluten, 21 which has displayed good mechanical material properties-gluten films can be made elastic, whereas most biopolymer materials are brittle. Another interesting aspect of avenin is that people suffering from celiac disease do not react to it, making it a more appropriate food packaging or coating material than gluten.…”
Section: Andmentioning
confidence: 99%